Investigating the effect a single dose of cannabidiol has on measures of stress in cats when being transported in a carrier and meeting a novel person in an unfamiliar environment - Weller, Jennifer E.; Flint, Hannah E.; Hunt, Alysia B. G.; Ellerby, Zack; King, Tammie (Frontiers in Veterinary Science, 2024)
Domestic cats (Felis Catus) are often exposed to stimuli that have the potential to negatively impact their welfare. These can include situations such as veterinary visits, travel, changes to their home environment, and interactions with unfamiliar people or pets. Cannabidiol (CBD)-infused pet products have grown in popularity in recent years, as pet owners search for ways to calm and relax their pets. However, research into the pharmacokinetic properties of CBD in cats is limited and investigations into its efficacy are in their infancy. The present study aimed to explore the effect of a single 4 mg/kg bodyweight dose of a THC-free CBD distillate on measures of stress in cats when experiencing a composite stress-paradigm, consisting of cat carrier travel and exposure to a novel person within an unfamiliar environment. Physiological and behavioural indicators of stress were collected pre-, during, and post-testing. No significant effect of CBD was observed on serum cortisol, IgA, or glucose, either before or immediately after the stress-paradigm (all p > 0.05). This was true despite cortisol being shown to significantly increase post-test for both treatments (both p < 0.001), suggesting that travel and meeting a novel person successfully induced a stress response within this population of cats. No significant differences in any measures of cat behaviour, including latency to approach the novel person, were observed between treatments (all p > 0.05). Overall, no influence of CBD was observed in cats, suggesting further research into appropriate dosage, delivery matrices, and other conditional factors, such as individual coping styles, should be considered.